Characterization of Poly: a novel mediator of insulin receptor signalling in drosophila. - Bolukbasi, Ekin (The University of Edinburgh, 2011)
Poly is a novel, essential protein in Drosophila melanogaster, loss of function of which results in late larval lethality. Importantly, Poly is evolutionarily conserved with a human homologue. poly mutation was isolated in a P-element mutagenesis screen that aimed to generate a larger collection of single P-element induced mutants. Mutant poly larvae are characterized by extreme larval longevity without pupation, formation of melanotic masses, smaller imaginal discs and brains, and abnormal nuclear morphology in neuroblasts. During the course of my project, I attempted to identify cellular processes and pathways that Poly might be involved in. Interestingly, my data suggest that Poly is a novel interactor and regulator of Insulin receptor/target of rapamycin (InR/TOR) signalling in Drosophila. Linking environmental cues to cell growth and metabolism is an essential process that multicellular organisms need to accomplish successfully for normal development. InR/TOR signalling is a highly conserved pathway that mediates the link between the environment and cellular processes such as growth, metabolism and ageing. My analysis in Drosophila suggests that Poly interacts physically with the InR and mutation of Poly leads to an overall down-regulation of InR/TOR signalling in Drosophila as revealed by decreases in the phosphorylation levels of Akt, S6K and 4E-BP - all downstream effectors of this pathway. In addition, loss of poly results in constitutive activation of autophagy in Drosophila fat body and a decrease in stored triglyceride levels. Furthermore, I show that localisation and levels of Poly protein are dependent on insulin action in both Drosophila and human cells. Together, these data suggest that Poly is a novel mediator of InR signalling that promotes an increase in cell growth and metabolism. Taking into consideration the observed poly mutant phenotype, I also investigated the potential involvement of Poly during cell cycle progression and the Drosophila innate immune response. While my analysis suggests that poly loss of function does not have a direct effect on cell cycle progression, alteration of Poly has consequences on various aspects of the Drosophila innate immune response. Therefore, I conclude that the Drosophila innate immune response is a cellular process in which Poly plays a crucial role.
Keywords: Poly; protein; drosophila; InR/TOR signalling; insulin; immune response